Prosaic conditions : Heinrich Heine and the spaces of Zionist literature - Rokem, Na'ama (Northwestern University Press, 2013)
In this book, the author observes that prose writing -- more than poetry, drama, or other genres -- came to signify a historic rift that resulted in loss and disenchantment. The author treats prose as a signifying practice -- that is, a practice that creates meaning. During the nineteenth and twentieth centuries, prose emerges in competition with other existing practices, specifically, the practice of performance. Using Zionist literature as a test case, the author examines the ways in which Zionist authors put prose to use, both as a concept and as a literary mode. Writing prose enables these authors to grapple with historical, political, and spatial transformations and to understand the interrelatedness of all of these changes.
Revision of the author's thesis (PhD)--Stanford University, 2007.
Keywords: Bialik, Hayyim Nahman, -- 1873-1934 -- Criticism and interpretation.; Herzl, Theodor, -- 1860-1904 -- Criticism and interpretation.; Heine, Heinrich, -- 1797-1856 -- Criticism and interpretation.; Hegel, Georg Wilhelm Friedrich, -- 1770-1831 -- Criticism and interpretation.; Bialik, Hayyim Nahman, -- 1873-1934; Hegel, Georg Wilhelm Friedrich, -- 1770-1831; Heine, Heinrich, -- 1797-1856; Herzl, Theodor, -- 1860-1904; Zionism in literature.; Prose literature -- Jewish authors -- History and criticism.; Prose -- Auteurs juifs -- Histoire et critique.; LITERARY CRITICISM -- General.; Zionism in literature; Languages & Literatures.; Literature - General.; Criticism, interpretation, etc.